The economics of economists : institutional setting, individual incentives and future prospects - Lanteri, Alessandro; Vromen, Jack J., 1958- (Cambridge : Cambridge University Press, 2014)
The profession of academic economics has been widely criticized for being excessively dependent on technical models based on unrealistic assumptions about rationality and individual behavior, and yet it remains a sparsely studied area. This volume presents a series of background readings on the profession by leading scholars in the history of economic thought and economic methodology. Adopting a fresh critique, the contributors investigate the individual incentives prevalent in academic economics, describing economists as rational actors who react to their intellectual environment and the incentives for economic research. Timely topics are addressed, including the financial crisis and the consequences for the discipline, as well as more traditional themes such as pluralism in research, academic organizations, teaching methodology, gender issues and professional ethics. This collection will appeal to scholars working on topics related to economic methodology and the teaching of economics.
Introduction / Alessandro Lanteri and Jack Vromen -- Part I. The Institutional Setting of Academic Economics: 1. The culture of academic economics / Arjo Klamer ; 2. The construction of a global profession: the transnationalization of economics / Marion Fourcade ; 3. Academic rankings between the'republic of Science' and'new public management' / Margit Osterloh and Bruno S Frey ; 4. Gatekeepers of economics: the network of editorial boards in economic journals / Alberto Baccini and Lucio Barabesi -- Part II. The Individual Incentives of Professional Economists: 5. Can European economics compete with U.S. economics? And should it? / David Colander ; 6. Career patterns of economics Ph. D.s: a decade of outcomes for the class of 1997 / Wendy Stock and John Siegfried ; 7. Scientific norms and the values of economists: the case of priority fights in economics / Wade Hands -- Part III. Challenges and Solutions: 8. Why economics is on the wrong track / Deirdre McCloskey ; 9. Do we try to teach our students too much? / Robert Frank; 10. The perils of narrative teaching in economics Jack Vromen; 11. Academic women's careers in the social sciences / Donna Ginther and Shulamit Kahn ; 12. Ought (only) economists to defect? Stereotypes, identity, and the prisoner dilemma / Alessandro Lanteri and Salvatore Rizzello ; 13. The financial crisis and the systemic failure of academic economics / David Colander, Hans Follmer, Armin Haas, Michael Goldberg, Katarina Juselius, Alan Kirman, Thomas Lux and Brigitte Sloth -- Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Economics -- Research; Economics -- Study and teaching (Higher)